Higher Education & Research in Africa – The Stakeholders - Havemann, Jo; Ksibi, Nabil; Maina, Mahmoud Bukar; Obanda, Johanssen; Okelo, Luke; Owango, Joy (My University, 2020)
List of stakeholders and research-related institutions in Africa and abroad. The list is continuously being updated and displayed at https://info.africarxiv.org/stakeholders/.
Keywords: stakeholders; Research in Africa; Higher Education